RANCANG SMART MIXING MENGGUNAKAN METODE HUMAN MACHINE INTERFACE (HMI ) DENGAN KONTROL PLC PADA PROSES MIXER ( PEMBUATAN ADONAN ROTI ) PT.NIPPON INDOSARI CORPINDO – PASURUAN - teguh pradana; eko Prastyo MAsdiansyah (SPIRIT, 2022)
Research at PT Nippon Indosari Corpindo Tbk on the background of observational data in the process of making bread on a mixer machine often occurs in formula input errors due to humam errors due to forgetfulness and indiscipline. The aim of this research is to find a solution. The method used in the study with a Fish bone diagram to identify factors that are likely to cause problems, From the results of food data management, focus improvement is done by creating SMART MIXING DESIGN USING HUMAN MACHINE INTERFACE (HMI) METHOD WITH PLC CONTROL IN MIXER PROCESS. A verification system so that the mixer operator does not forget / wrong in entering the raw material for the bread material during the mixer process.